2021
DOI: 10.1016/j.ejro.2021.100378
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of multiple b-value diffusion-weighted images and T1 post enhancement magnetic resonance imaging images fusion with Laplacian Re-decomposition (LRD) medical fusion algorithm for glioma grading

Abstract: Background: Grade of brain tumor is thought to be the most significant and crucial component in treatment management. Recent development in medical imaging techniques have led to the introduce non-invasive methods for brain tumor grading such as different magnetic resonance imaging (MRI) protocols. Combination of different MRI protocols with fusion algorithms for tumor grading is used to increase diagnostic improvement. This paper investigated the efficiency of the Laplacian Re-decomposition (LRD) fusion algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Interestingly, in fused images, RSCs in LGGs are significantly higher than HGGs with PCA, DCHWT, LRD, and DDcGAN algorithms. These values correlate satisfactorily with previous studies and further support the role of tumor cellularity and micro bleeding in HGGs 4 , 5 , 33 . In accordance with the present results, previous studies have demonstrated that tumor cellularity increased with glioma grade, and HGGs have lower ADC values in DWI images than LGGs 34 36 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, in fused images, RSCs in LGGs are significantly higher than HGGs with PCA, DCHWT, LRD, and DDcGAN algorithms. These values correlate satisfactorily with previous studies and further support the role of tumor cellularity and micro bleeding in HGGs 4 , 5 , 33 . In accordance with the present results, previous studies have demonstrated that tumor cellularity increased with glioma grade, and HGGs have lower ADC values in DWI images than LGGs 34 36 .…”
Section: Discussionsupporting
confidence: 90%
“…Three ROIs were sampled and averaged for each region to improve the comparison's power. Then, RSC was calculated by the following equation 5 , 33 : Is the mean signal intensity of the active tumor region, and Is the mean signal intensity of the white matter in each picture. RSCs in fused images of LGGs and HGGs with different fusion methods were calculated and compared with each other for glioma grading performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the research finds out the result on CET1w MRIs have the better classifying performance. The reason may be that there are significant differences in the average relative signal strength on CET1w images between HGG and LGG (Khorasani et al 2021). Although CET1w has traditionally been a marker of high grade gliomas (Scott et al 2002), previous studies reported that 14%-45% of nonenhancing supratentorial gliomas are malignant (Mihara et al 1995, Barker et al 1997, Ginsberg et al 1998, Scott et al 2002 and some enhancing gliomas (i.e.…”
Section: Validation Of the Proposed Approachmentioning
confidence: 99%